2019
DOI: 10.1080/00952990.2019.1669629
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the composition of the human intestinal microbiome in alcohol use disorder: a systematic review

Abstract: Background: A growing body of evidence highlights the role of the intestine in the development of various alcohol use disorder (AUD) complications. The intestinal microbiome has been proposed as an essential factor in mediating the development of AUD complications such as alcoholic liver disease. Objectives: To provide a comprehensive description of alcohol-induced intestinal microbiome alterations. Methods: We conducted a systematic review of studies investigating the effect of alcohol on the intestinal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…Alcohol consumption is also associated with a reduction of anti-inflammatory molecules, such as IL-10 ( 37 ), which may further aggravate the COVID-19-associated lung inflammation and established dysregulation in the anti-inflammatory immune response ( 24 ). Besides, alcohol consumption modulates the gut microbiome ( 38 ), and curbs the viral immune response ( 39 ), which may expose the individual to SARS-CoV-2 gastrointestinal infection ( 40 , 41 ), leading to, increased gastrointestinal dysbiosis ( 42 ) and more severe respiratory complication due to COVID-19 ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption is also associated with a reduction of anti-inflammatory molecules, such as IL-10 ( 37 ), which may further aggravate the COVID-19-associated lung inflammation and established dysregulation in the anti-inflammatory immune response ( 24 ). Besides, alcohol consumption modulates the gut microbiome ( 38 ), and curbs the viral immune response ( 39 ), which may expose the individual to SARS-CoV-2 gastrointestinal infection ( 40 , 41 ), leading to, increased gastrointestinal dysbiosis ( 42 ) and more severe respiratory complication due to COVID-19 ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the microbiome (dysbiosis) has been linked with a wide range of conditions including diabetes, obesity, cardiovascular disease, inflammatory bowel disease and liver cirrhosis; however, it is unclear whether this is a cause or effect relationship [ 13 , 14 ]. Several studies have investigated the effect of alcohol consumption in both animal and human models, and have consistently shown that alcohol consumption is linked with the development of dysbiosis [ 13 , 15 ]. In brief, alcohol has been shown to increase the relative abundance of Proteobacteria , Enterobacteriacea and Streptococcus and decrease the abundance of Bacteroides , Akkermansia and Faecalibacterium [ 15 ].…”
Section: Alcohol and The Gutmentioning
confidence: 99%
“…Several studies have investigated the effect of alcohol consumption in both animal and human models, and have consistently shown that alcohol consumption is linked with the development of dysbiosis [ 13 , 15 ]. In brief, alcohol has been shown to increase the relative abundance of Proteobacteria , Enterobacteriacea and Streptococcus and decrease the abundance of Bacteroides , Akkermansia and Faecalibacterium [ 15 ]. The aetiological mechanism of this dysbiosis is not fully understood; however, it is likely that this is multifaceted, including alcohol-induced oxidative stress (which is poorly tolerated by obligate anaerobes such as Bacteroides ) and the downregulation of antibacterial peptides such as α-defensins by alcohol [ 16 , 17 ].…”
Section: Alcohol and The Gutmentioning
confidence: 99%
“…Inconsistent with the results of the above study, the abundance of Bifidobacterium increased significantly after heat shock in the present study. In an experiment assessing alcohol damage to the intestine, and the abundance of Bifidobacterium was observed to increase 29 . Faecalibaculum belongs to the phylum Firmicutes and is involved in inflammation regulation and lipid metabolism 30 .…”
Section: Discussionmentioning
confidence: 99%